2018
DOI: 10.7717/peerj.5296
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the endangered basal angiospermBrasenia schreberi(Cabombaceae) in China

Abstract: Brasenia schreberi J.F. Gmelin (Cabombaceae), an aquatic herb that occurs in fragmented locations in China, is rare and endangered. Understanding its genetic diversity and structure is crucial for its conservation and management. In this study, 12 microsatellite markers were used to estimate the genetic diversity and variation in 21 populations of B. schreberi in China. A total of 61 alleles were found; assessment of allelic richness (Ar = 1.92) and observed and expected heterozygosity (HO = 0.200, HE = 0.256)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…In the present study, I. yunguiensis showed high genetic diversity compared with other rare, endemic, and endangered plants, such as Isoetes sinensis Palmer (He = 0.118; Kang, Ye & Huang, 2005) Liu et al, 2019), and Brasenia schreberi J. F. Gmelin (He = 0.256; Li et al, 2018). Most rare and endangered plants are seed plants that can achieve a higher gene flow via long-distance pollen and seed dispersal than ferns that rely solely on spores.…”
Section: Genetic Diversity and Structurementioning
confidence: 50%
“…In the present study, I. yunguiensis showed high genetic diversity compared with other rare, endemic, and endangered plants, such as Isoetes sinensis Palmer (He = 0.118; Kang, Ye & Huang, 2005) Liu et al, 2019), and Brasenia schreberi J. F. Gmelin (He = 0.256; Li et al, 2018). Most rare and endangered plants are seed plants that can achieve a higher gene flow via long-distance pollen and seed dispersal than ferns that rely solely on spores.…”
Section: Genetic Diversity and Structurementioning
confidence: 50%
“…A high degree of genetic differentiation among populations accounted for approximately 54% of the total genetic diversity (G ST = 0.544, AMOVA, P=45%), so both within-population diversity and diversity among populations contributed significantly to the total diversity of the species. Other species also showed high diversity among populations, such as Argania spinosa L. Skeels ( Mouhaddab et al, 2017 ), Brasenia schreberi ( Li et al, 2018 ), and Pelatantheria scolopendrifolia ( Yun et al, 2020 ). Yun et al (2020) showed that geographic isolation, low gene flow and asexual reproduction were related to the high divergence among Pelatantheria scolopendrifolia populations.…”
Section: Discussionmentioning
confidence: 99%
“…The low estimated value of Nm (0.419) among I. serracarajensis populations and the significant correlation between geographical and genetic distances (Mantel r = 0.821, P < 0.0001) indicate that the geographical isolation barrier could principally affect gene flow. In fact, the Mantel test is reliable for determining the correlation between genetic and geographical distances among populations such as Ottelia acuminate var jingxiensis ( Li et al, 2019 ) and Brasenia schreberi ( Li et al, 2018 ). Spores of Isoetes are scattered gradually through the decay of sporangial tissue, and the proximity of megasporangia and microsporangia enables significant intergametophytic selfing analogous to self-pollination in seed plants ( Caplen & Werth, 2000 ), which could contribute to lower genetic diversity in neighbouring plants and greater genetic diversity in distant plants, as shown for the endangered Isoetes hypsophila Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…High genetic diversity and admixture in Warburgia salutaris. Assessment of genetic diversity is critical to understand the ability of a species to cope with changing conditions and environments, especially for threatened species 39,[64][65][66][67][68] . In this study, we reported for the first time the development of Single Sequence Repeats (SSR) markers in W. salutaris by employing next generation sequencing (Illumina platform).…”
Section: Discussionmentioning
confidence: 99%